Fenêtre sur cour. - Fricke, Harald; Kahrs, Johannes (Paris : Galerie Almine Rech, 1997)
Alpern, Merry ; Doberauer, Anke ; Post, Linda ; Kahrs, Johannes ; Huynh, Jean-Baptiste ; Rondinone, Ugo ; Stidworthy, Imogen ; Samore, Sam ; Hyber, Fabrice ; Sarcevic, Bojan ; Bournigault, Rebecca ; Calle, Sophie
biografie
Fenêtre sur cour, Galerie Almine Rech, Paris, 1.04.97 - 17.05.97
Duits
boek